Determination of beta-defensin genomic copy number in different populations: a comparison of three methods. - Peder Fode; Cathrine Jespersgaard; Robert J Hardwick; Helen Bogle; Michael Theisen; Daniel Dodoo; Martin Lenicek; Libor Vitek; Ana Vieira; Joao Freitas; Paal Skytt Andersen; Edward J Hollox (PLoS ONE)
Background There have been conflicting reports in the literature on association of gene copy number with disease, including CCL3L1 and HIV susceptibility, and β-defensins and Crohn's disease. Quantification of precise gene copy numbers is important in order to define any association of gene copy number with disease. At present, real-time quantitative PCR (QPCR) is the most commonly used method to determine gene copy number, however the Paralogue Ratio Test (PRT) is being used in more and more laboratories. Findings In this study we compare a Pyrosequencing-based Paralogue Ratio Test (PPRT) for determining beta-defensin gene copy number with two currently used methods for gene copy number determination, QPCR and triplex PRT by typing five different cohorts (UK, Danish, Portuguese, Ghanaian and Czech) of DNA from a total of 576 healthy individuals. We found a systematic measurement bias between DNA cohorts revealed by QPCR, but not by the PRT-based methods. Using PRT, copy number ranged from 2 to 9 copies, with a modal copy number of 4 in all populations. Conclusions QPCR is very sensitive to quality of the template DNA, generating systematic biases that could produce false-positive or negative disease associations. Both triplex PRT and PPRT do not show this systematic bias, and type copy number within the correct range, although triplex PRT appears to be a more precise and accurate method to type beta-defensin copy number.